Pelatihan dan Pembelajaran Metode Riset Aksi Partisipatoris Untuk Pemajuan Kebudayaan - Paschalis Maria Laksono (Faculty of Cultural Sciences, 2018)
Sumba as one of the 3T (Tertinggal/Disadvantaged, Terdepan/frontmost, Terluar/Outermost)regions in Indonesia has a crisis of acculturation in its development, where local customs andculture are no longer able to meet the demands of renewal of the development. Many scholars haveconducted research and studies on Sumba and meanwhile, not a few Sumba people go outside Sumbato study and are expected to bring change to the land of Sumba. However, the crisis still occurs.Community Action Plans (CAP) are a way for the community to participate in the development.What is often questioned is the quality of the CAP itself which was conceived as a bottom-up eﬀortin the development. Anthropology with its ethnographic methods and holistic participatory researchmethods can enrich the CAP to structure it to be more qualifed by considering the principles ofcultural advancement.Tis training and learning of participatory action research methods oﬀer a way to explore sociocultural capitals as the identity of the community to adjust to the changing times that occur throughdevelopment. Te Sumba student community who are studying in Yogyakarta and its surroundingsare invited to play a role through the training and learning of the CAP-based culture promotionmethod so that they are expected to become pioneers in the development of Sumba culture throughactive community participation in Sumba. In addition, the Sumba community is expected to changeas the times progress towards a more prosperous world without leaving their identity as Sumba people.